Media Agenda on Yogyakarta Sultanate Succession - Nasionalita, Kharisma; Nugroho, Catur (Jurnal Kajian Jurnalisme, 2020)
Yogyakarta is a province with special status in Indonesia, bound by unique local political rules. According to The Mandate of Law Number 13 of 2012 concerning the Privileges of Yogyakarta, the position of Governor and Deputy Governor must be filled by the determined leaders of the palace. Yogyakarta's local politics went under the spotlight when Sultan Hamengku Buwono crowned his eldest daughter to be the successor to the palace's leadership in his Sabdatama (Kings Order). National regulation does not mention the gender of the Governor and Deputy Governor while in the internal court of the Yogyakarta palace, the position of a leader must be occupied by men. The issue gained intensive national media attention throughout March-May 2015, particularly by Kompas, Republika, and Kedaulatan Rakyat. This research aims to measure the media agenda related to the issue of the Sultanate succession on three selected newspapers. Through the quantitative content analysis method, this research dissects how the media places and emphasizes this issue. The purpose of this research is to identify how issues are prioritized through news content.  There are 62 news articles selected from the period March-May 2015. The result of the research shows that all media emphasizes the Sultanate issue in different ways.  There is a distinction between the local newspaper Kedaulatan Rakyat and the national newspaper (KOMPAS and Republika). The local newspaper put monarchy issue in the second rank while the national newspaper set constitutional issues such as the polemic prerequisite of Yogyakarta Governor and Deputy Governor in second place.